Ramly – Dato’ Dr. Hj. Ramly Bin Mokni / Nik Anis Syuhada Nik Abdul Aziz - Nik Abdul Aziz, Nik Anis Syuhada (2021)
Ramly Burger was one of Malaysia's local brand franchises, founded by a husband and wife, Dato Dr. Haji. Ramly bin Mokni and Datin Hajiah Shala Bint Abdul Manap. I chose Dato’ Dr. Haji Ramly bin Mokni because I appreciated my efforts to get his company from a small business to a profitable local Malaysian franchise. The company was started in 1979 at Lorong Haji Hussin in Kuala Lumpur, once a small business.